Fluorescence Quenching of Tyrosine-Ag Nanoclusters by Metal Ions Analytical and Physicochemical Assessment - Ungor Ditta Ditta (INTERNATIONAL JOURNAL OF MOLECULAR SCIENCES, 2022)
A new synthesis method is described for the first time to produce silver nanoclusters (AgNCs) by using the tyrosine (Tyr) amino acid. Several important parameters (e.g., molar ratios, initial pH, reaction time etc.) were optimized to reach the highest yield. The formed Tyr-AgNCs show characteristic blue emission at λem = 410 nm, and two dominant fluorescence lifetime components were deconvoluted (τ1 ~ 3.7 and τ2 ~ 4.9 ns). The NCs contained metallic cores stabilized by dityrosine. For possible application, the interactions with several metal ions from the tap water and wastewater were investigated. Among the studied cations, four different ions (Cu2+, Ni2+, Fe3+, and Rh3+) had a dominant effect on the fluorescence of NCs. Based on the detected quenching processes, the limit of detection of the metal ions was determined. Static quenching (formation of a non-luminescent complex) was observed in all cases by temperature-dependent measurements. The calculated thermodynamic parameters showed that the interactions are spontaneous ranked in the following order of strength: Cu2+ > Fe3+ > Rh3+ > Ni2+. Based on the sign and relations of the standard enthalpy (ΔH°) and entropy changes (ΔS°), the dominant forces were also identified.